IMPLICIT EXPRESSION OF IMPERATIVE MOOD IN ADVERTISING TEXTS - Ne’matova Iroda Ilhom qizi (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
All languages change over time and change is inevitable for any living language. History records that languages change over time at every level of structure which includes vocabulary, phonology, morphology and syntax. For many people, it may not be easily apparent or obvious in a day-to-day communication on a personal level because many individuals are so intimately connected to their language that they may fail to see its changes. However, languages do indeed change and some languages flourish, some expand and some languages even die.